A Wireless controlled semi-autonomous fire extinguishing robot to rescue and monitor hazardous - Imran Bin, Jafar; Raihana, Kanij; Barua, Tanwy; Uddin, Milon (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2013.